Reti d’impresa ambientali e innovazione: un’applicazione per l’Italia - Guarini, Giulio; Garofalo, Giuseppe; Moschetti, Arianna (Argomenti, 2017)
This paper analyzes the drive function that business networks in environmental field can play with reference to innovative processes. In the theoretical section, based on an approach that combines Schumpeter's intuitions with the evolutionist authors' suggestions, we highlight the importance of environmental innovations for sustainable economic growth. Analyzing the driver of environmental innovations, we focus on the importance of networks where, as in Italy, the production structure is characterized by the presence of SMEs. In the empirical section, we build a database of the environmental business networks in Italy and carry out an econometric study in order to measure the impact of formally formed agreements on the productivity of individual participating companies